Comparison of Subjective and Objective Cognitive Function and Emotional State in Supratentorial Brain Tumors Before Surgery—Recognizing the Influence of Laterality - Lisa Schock; Karsten Wrede; Neriman Oezkan; Philipp Dammann; Marvin Darkwah Oppong; Oliver Gembruch; Ramazan Jabbarli; Ilonka Kreitschmann‐Andermahr; Sonja Siegel; Anna Lena Friedel; Adrian Engel; Hanah Hadice Karadachi; et al. (Cancer Medicine)
ABSTRACT Objective Because of its high prognostic value, neuropsychological assessment plays a crucial role in the neuro‐oncology setting. Subjective and objective cognitive performance correlate only to a limited extent, and subjective cognitive performance is strongly dependent on emotional state. We postulate that the relation of subjective and objective cognitive performance depends on tumor laterality. Methods In this prospective study, N = 63 patients with brain tumors underwent a neuropsychological test battery, including assessment of subjective cognitive function (attention, memory, executive), and symptoms of depression and anxiety before surgery. Patients with psychiatric comorbidity or severe neurological conditions were excluded. Results There were no significant differences in subjective and objective cognitive function, symptoms of depression and anxiety between left (N = 37) and right (N = 26) hemisphere tumors. All measures of subjective cognitive function correlated highly significantly with symptoms of depression and anxiety in left hemisphere tumor patients (all r ≥ 0.470). In right hemisphere tumor patients, there was no relation between subjective cognitive function and emotional state. Significant laterality differences for correlations of subjective and objective cognitive function were not found and were not significant within the two groups. Conclusions Even when unbiased by symptoms of anxiety and depression, right hemisphere tumor patients show the same discrepancy in subjective and objective cognitive function as left hemisphere tumor patients. This discrepancy may be based on a different mechanism in right hemisphere tumor patients.